Mathematical model of inertial-optical autonomous navigation complex of unmanned aerial vehicle - A. A. Sheinikov; V. A. Malkin (Системный анализ и прикладная информатика, 2022)
In the article considers the possibility of implementing an autonomous mode in the navigation complex of a small-sized tactical unmanned aerial vehicle, including a strapdown inertial navigation system and an onboard vision system. Due to the fact that the accuracy of such navigation systems significantly depends on changes in the background-target environment and equipment failures, it is proposed to organize automatic adaptation of the system to changes in external conditions and internal factors by controlling the operating modes and parameters of the software that implements optimal estimation algorithms. For this purpose, a model of an onboard inertial-optical autonomous navigation system has been developed in the class of discrete dynamic systems with a random change in structure.